Temporary Diverting End-Colostomy in Critically Ill Children with Severe Perianal Wound Infection. (June 2021) - Gün, Emrah; Kendirli, Tanil; Botan, Edin; Özdemir, Halil; Çiftçi, Ergin; Konca, Kübra; Koloğlu, Meltem; Göllü, Gülnur; Can, Özlem Selvi; Tutar, Ercan; Akar, Ahmet Rüçhan; İnce, Erdal
Abstract : ABSTRACT: Broad and deep perianal wounds are challenging in both adult and pediatric ICUs. These wounds, if contaminated with gastrointestinal flora, can cause invasive sepsis and death, and recovery can be prolonged. Controlling the source of infection without diverting stool from the perianal region is complicated. The option of protective colostomy is not well-known among pediatric critical care specialists, but it can help patients survive extremely complicated critical care management. These authors present three critically ill children who required temporary protective colostomy for perianal wounds because of various clinical conditions. Two patients were treated for meningococcemia, and the other had a total artificial heart implantation for dilated cardiomyopathy. There was extensive and profound tissue loss in the perianal region in the patients with meningococcemia, and the patient with cardiomyopathy had a large pressure injury. Timely, transient, protective colostomy was beneficial in these cases and facilitated the recovery of the perianal wounds. Temporary diverting colostomy should be considered as early as possible to prevent fecal transmission and accelerate perianal wound healing in children unresponsive to local debridement and critical care.